Amphibians and Reptiles Diversity in Bukit Baka Bukit Raya National Park, West Kalimantan - Kennedi, Umar Fhadli; Zainudin; Purwanto, Sigit; Jakaria, Mohamad; Kusrini, Mirza Dikari; Prabowo, Oktavianus Jekki; Yanto, A Viktor; Maddock, Simon T (Media Konservasi, 2024)
Studies related to herpetofauna diversity in the Bukit Baka Bukit Raya National Park (Tanakaya), West Kalimantan are very limited. Data related to the richness of amphibians and reptiles in this area are important for the management of the area in the future. We conducted amphibian and reptile surveys in Tanakaya in July-August 2019 using Visual Encounter Survey methods at five sites (Belaban Resort: Km 37 & 39; Resort Rantau Malam: Batu Lintang, Sungai Mangan, and Hulu Rabang). We recorded 50 amphibian species from nine families and 25 reptile species from seven different families. Twenty of these species are new records for Tanakaya. The highest diversity (H' = 2.94) was found in Batu Lintang, while the highest evenness (E = 0.55) was in Sungai Mangan, and the highest community similarity index (IS = 0.6) was in Batu Lintang with Km 37. Combined with previous studies, there have been 142 species (78 species of amphibians and 64 species of reptiles) recorded from Tanakaya. Further study is needed to fully understand the herpetofauna in Tanakaya, but our data highlights the importance of the national park for preserving global biodiversity.